If Donald Trump were Mexican, would he still be Donald Trump? The problem of identity in counterfactuals and a dispositionalist solution - Casini, Giulia (Rivista Italiana di Filosofia del Linguaggio)
The study of counterfactuals has produced some well-known problems concerning identity. I focus on two of them. I suggest that a dispositionalist account of counterfactuals, not involving possible worlds but dispositions and potentiality, could solve both. First is the problem of identity across possible worlds, concerning the identification of individuals in various possible worlds. Dispositionalism can solve it: its aim is to explain counterfactuals in the actual world, without appealing to possible worlds. This would eliminate the problem because the individuals involved in counterfactuals would be in the actual world, without needing identification in other worlds. Second is the problem of what I call ‘property alteration’. In ‘if Donald Trump were Mexican, he wouldn’t be President of the USA’, denying Trump’s property of ‘being a US citizen’ could lead us to deny the identity between the Donald Trump we know and the Donald Trump of the counterfactual. Barbara Vetter’s version of dispositionalism can solve also this problem, introducing the concept of ‘potentiality’.